CTL-Derived Exosomes Enhance the Activation of CTLs Stimulated by Low-Affinity Peptides - Wu, Shu-Wei; Li, Lei; Wang, Yan; Xiao, Zhengguo (Frontiers in Immunology, 2019)
Cytotoxic T cells (CTLs) bind to peptides presented by MHC I (pMHC) through T cell receptors of various affinities. Low-affinity CTLs are important for the control of intracellular pathogens and cancers; however, the mechanisms by which these lower affinity CTLs are activated and maintained are not well understood. We recently discovered that fully activated CTLs stimulated by strong-affinity peptides in the presence of IL-12 are able to secrete exosomes that, in turn, stimulate bystander CTLs without requiring the presence of antigen. We hypothesized that exosomes secreted by high-affinity CTLs could strengthen the activation of low-affinity CTLs. Naive OT-I CD8+ cells were stimulated with altered N4 peptides of different affinities in the presence or absence of Exo. The presence of Exo preferentially increased cell proliferation and enhanced the production of IFNγ in CTLs stimulated by low-affinity peptides. The expression of granzyme B (GZB) was augmented in all affinities, with higher GZB production in low-affinity stimulated CTLs than in high-affinity stimulated ones. Exosomes promoted the rapid activation of low-affinity CTLs, which remained responsive to exosomes for a prolonged duration. Unexpectedly, exosomes could be induced quickly (24 hours) following CTL activation and at a higher quantity per cell than later (72 hours). While exosome protein profiles vary significantly between early exosomes and their later-derived counterparts, both appear to have similar downstream functions. These results reveal a potential mechanism for fully activated CTLs in activating lower-affinity CTLs that may have important implications in boosting the function of low-affinity CTLs in immunotherapy for cancers and chronic viral infections.